Conversational AI in E-Commerce: Strategic Implications of Voice-Based Chatbots for Consumer Engagement and Trust - Gharib, Moaz; Trivedi, Vibha; Trivedi, Ashish (International Review of Management and Marketing, 2025)
AI-powered chatbots are disruptive innovations with great potential for easing online business communication. This study aims to empirically investigate the influence of the voice mode of chatbot technology on consumer continuance intention toward e-commerce websites by examining the role of perceived technological optimism (PTO), cognition-based trust (CBT), and perceived customer care (PCC). A 2X2 factorial design is employed for a between-subjects laboratory experiment. ANOVA was used to test the treatments’ comparative effects, and the final analyses were done using Hayes PROCESS Macro in SPSS. The results reveal consumer preference for the voice mode of chatbots over the text mode when seeking service assistance. It empowers consumers by giving them greater control over their interaction with technology and the problem-solving process. With a seamless interaction with a virtual assistant, consumers develop CBT in the technology, leading to positive PCC and, eventually, continuance intention toward the website. The study offers recommendations on how to save a firm’s resources by retaining its customers rather than spending on new acquisitions. Firms need to implement a competent technology that allows customers to express themselves using autonomy, thereby building trust and continued engagement.